Hexagonal deformation-quadrilateral dot matrix energy absorption structure
By designing the six-deformed-quadrilateral lattice energy absorption structure, adjusting the shape and connection of cell units and increasing the plastic hinge, the traditional energy absorption structure has been solved in terms of energy absorption efficiency and stability, and a higher specific energy absorption is achieved Performance and stability.
Patent Information
- Application Number
- CN202411451660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional energy-absorbing structures have limitations in bearing capacity and energy absorption efficiency, especially the flat-top pyramid structure needs to be improved in further improving energy absorption efficiency and reducing structural quality.
A six-deformed-quadrilateral lattice energy-absorbing structure was designed. Based on the secondary design of the flat-top pyramid, the bottom shape of the cell unit is adjusted and the connection between the cell unit is optimized, and the structure is improved by increasing the plastic hinge. Energy absorption capacity forms a close-connected arrangement structure.
The energy absorption capacity and energy absorption performance of the lattice energy-absorbing structure are improved, and are especially suitable for application scenarios that require high specific energy absorption and good stability, showing mechanical properties and stability that are better than flat-topped pyramid structures.
Smart Images

Figure CN119122973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of structural engineering, in particular to a six-deformation quadrilateral lattice energy absorption structure. Background Art
[0002] With the development of engineering technology and materials science, energy-absorbing structures are increasingly used in transportation, construction engineering, aerospace and other fields. Especially in terms of collision protection, seismic design and structural lightweighting, the research on energy-absorbing structures is particularly important. Traditional energy-absorbing structures mostly use various honeycomb structures and grid structures, but they have limitations in bearing capacity and energy absorption efficiency. At the same time, in the existing technology, the flat-top pyramid structure performs well in impact energy absorption due to its low center of mass and good stability. However, in order to further improve its energy absorption efficiency and reduce the structural mass, it is necessary to improve the flat-top pyramid structure.
[0003] Therefore, there is an urgent need to develop a lattice energy absorption structure with higher specific energy absorption and mass efficiency. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a six-deformation quadrilateral lattice energy absorption structure, which is based on the secondary design of the flat-top pyramid, adjusts the bottom shape of the cell unit and optimizes the connection between the cell units, thereby improving the energy absorption capacity of the lattice energy absorption structure and ensuring the energy absorption performance of the lattice energy absorption structure, which is particularly suitable for application scenarios requiring high specific energy absorption and good stability.
[0005] To achieve the above object, the present invention provides the following solutions: A six-deformation quadrilateral lattice energy absorption structure is redesigned based on a flat-top pyramid structure. The lattice energy absorption structure is formed by a plurality of interconnected cell units distributed in an array along the z-axis. Each of the cell units has a hexagonal bottom surface and a quadrilateral top surface, and the structural shape of the entire cell unit is a prism.
[0006] Preferably, the length, width and height of each cell unit are limited to 10×10×10 mm. 3 The structure is in a cube, and the thickness of each cell unit is 1 mm.
[0007] Preferably, the top of each cell unit is inscribed in a 5×5 mm 2 The height of each cell unit is 10 mm, and the total height is 40 mm.
[0008] Preferably, the hexagonal bottom surface is circumscribed to a square, the shape of the quadrilateral top surface is a square, and the side length of the quadrilateral top surface is smaller than the side length of the square circumscribed to the hexagonal bottom surface.
[0009] Preferably, the side length of the hexagonal bottom surface and the side length of the quadrilateral top surface of the cell unit are both 5 mm.
[0010] Preferably, the edges of each of the cell units are tightly connected to the edges of adjacent cell units to form a close-fitting arrangement structure, so as to improve the energy absorption capacity of the structure by increasing plastic hinges.
[0011] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects: (1) The design of the six-deformation quadrilateral lattice energy absorption structure (HQLS) of the present invention is based on the bionics principle in nature, especially the geometric shape and stability of the flat-topped pyramid. In this design, the lattice energy absorption structure adopts a secondary design method to reduce the mass while improving the specific energy absorption performance. Due to its low center of mass characteristic, the flat-topped pyramid can show good stability and energy absorption effect under the action of external loads. Through the study of the flat-topped pyramid unit cell structure, it is found that there are mutual constraints and influences between its faces and between the cells, which provides a basis for further improving its energy absorption capacity.
[0012] (2) According to the super-folded unit theory, the lattice energy absorption structure absorbs the energy generated during dynamic impact through the deformation of plastic hinges. Therefore, by increasing the number of plastic hinges in the unit cell structure of the flat-top pyramid, its overall energy absorption performance will be effectively improved. In the structural design, maintaining close connections between adjacent cells, that is, the interconnection between the edges, helps to improve the overall stability and bearing capacity of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0014] Figure 1 A schematic diagram of the structural dimensions of a six-deformation quadrilateral lattice energy absorption structure of the present invention; Figure 2 A schematic diagram of a quasi-static axial compression finite element model of the HQLS lattice energy absorption structure provided by the present invention; Figure 3 A comparison diagram of the HQLS lattice energy absorption structure provided by the present invention before and after the compression test; Figure 4 A comparison chart of the grid convergence analysis and test results of the HQLS lattice energy absorption structure provided by the present invention; Figure 5This is a timing diagram of the quasi-static compression deformation of the HQLS lattice energy absorption structure provided by the present invention after filling; Figure 6 This is a comparison diagram of the HQLS lattice energy absorption structure test and simulation structure at a height of 100 mm provided by the present invention. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0017] Embodiment 1 like Figure 1 As shown, the present invention provides a six-deformation quadrilateral lattice energy absorption structure (hereinafter referred to as HQLS), which is secondary designed based on the flat-top pyramid structure. The lattice energy absorption structure is formed by a plurality of interconnected cell units distributed along the z-axis array. Each cell unit has a hexagonal bottom surface and a quadrilateral top surface, and the structural shape of the entire cell unit is a prism. At the same time, the length, width and height of each cell unit are limited to 10×10×10mm 3 The top of each unit cell is inscribed in a 5×5mm cube. 2 The hexagonal base is circumscribed to the square, the quadrilateral top is a square, and the side length of the quadrilateral top is less than the side length of the circumscribed square of the hexagonal base. b The length of the side of the quadrilateral top a are all 5mm, and the unit height of the pyramidal cell is set to h =5mm, the unit structure of a single cell is a prism mirrored along the xOy plane, and its height is 2 h , and then the cell unit structure is closely arranged, and the edges of each cell unit are closely connected with the edges of the adjacent cell units to form a close arrangement structure, so as to improve the energy absorption capacity of the structure by increasing the plastic hinge. Finally, the array is distributed along the z-axis to reach the required height to obtain the HQLS lattice energy absorption structure, in which the height of each cell unit is 10mm and the total height is 40mm.
[0018] In the following, a combination of finite element simulation and experiment is used to verify the validity of the finite element model through quasi-static compression test, and to verify the deformation mode and mechanical properties of the HQLS lattice energy absorption structure during the crushing process.
[0019] First, based on the above content, a finite element model of the L64 lattice energy absorption structure was constructed, and LS-Dyna was used to simulate the constructed lattice energy absorption structure. The thickness was set to 1 mm, and the finite element model of the HQLS lattice energy absorption structure was obtained as shown in the figure. Figure 2 As shown in the figure, the HQLS lattice energy absorbing structure is placed on a rigid wall, and no constraints are set at its bottom. The purpose of the rigid wall is to obtain the data of the axial force during the compression process. At the same time, the friction coefficient between the HQLS lattice energy absorbing structure and the rigid wall is set to 0.3. A pressure plate with a constant speed of 2m / s is applied above the HQLS lattice energy absorbing structure. The pressure plate adopts a rigid shell unit and the compression distance is 24mm to achieve the height of the densification of the lattice energy absorbing structure. At the same time, automatic surface-to-surface contact is applied between the pressure plate and the HQLS lattice energy absorbing structure, and the friction coefficient is set to 0.3, thereby constructing a finite element model of the HQLS lattice energy absorbing structure.
[0020] In addition, in this embodiment, the obtained HQLS lattice energy absorption structure is subjected to a quasi-static compression test on an MTS hydraulic testing machine. The compression speed is set to 2mm / min, the compression amount is 24mm, and it accounts for 60% of the total length. At the same time, before the test, the HQLS lattice energy absorption structure needs to be heat treated. The test results are as follows: Figure 3 As shown in the figure, the deformation of the lattice energy absorbing structure during compression, the middle layer gradually extends outward and bulges during the extrusion process. As the compression displacement increases, cracks appear in the cone angle of the cell unit. During axial compression, the units on the left and right sides of the second and third layers bulge outward, bend and squeeze toward the symmetry axis, while the middle unit only undergoes compression deformation in the axial direction. Therefore, the HQLS lattice energy absorbing structure exhibits an "X"-shaped deformation as a whole. In this regard, referring to Table 1, by comparison, the mechanical properties of the HQLS lattice energy absorbing structure are better than those of the flat-top pyramid structure.
[0021] Table 1 Comparison of mechanical properties between HQLS lattice energy absorption structure and flat-top pyramid structure
[0022] In addition, refer to Figure 4 The deformation process of the HQLS lattice energy absorption structure used in this embodiment is mainly divided into three stages: linear elastic stage, platform stage and compaction stage. Figure 4The AB segment in the middle shows the linear elastic stage of the lattice energy absorbing structure. During the quasi-static compression process, the lattice energy absorbing structure did not show obvious peak force, and the compression process was relatively smooth. The BC segment is a platform segment, and its energy absorption process is relatively stable. A platform force appears, and the lattice energy absorbing structure begins to undergo plastic deformation. After point C is the compaction stage, the axial force gradually increases, the lattice energy absorbing structure becomes densified, and the stage in which the lattice energy absorbing structure dissipates energy through plastic deformation is basically over. In this stage, the axial force increases. At the same time Figure 4 The force displacement curves under different mesh sizes are given, mainly including 0.5mm, 1mm, 1.5mm and 2mm meshes. Figure 4 It can be seen that when the mesh size is different, the force-displacement curve increases with the increase of the mesh size.
[0023] Secondly, by verifying the effect of different mesh sizes on the mechanical parameters of the finite element model of the HQLS lattice energy absorption structure and the error of the quasi-static compression test, the results are shown in Table 2.
[0024] Table 2 Convergence accuracy comparison of HQLS lattice energy absorption structure
[0025] It can be seen from Table 2 that when the grid size is 1 mm, the errors of various mechanical parameters are less than 4%. Therefore, this embodiment selects 1 mm as the grid size of the lattice energy absorption structure. At the same time, the error between the test and the simulation is small, and it is believed that the finite element model constructed in this embodiment has high reliability.
[0026] In addition, refer to Figure 5 In this embodiment, a quasi-static compression test is also performed on a lattice energy absorbing structure with a height of 100 mm, i.e., for filling the interior of the mixing tube, in order to compare the ability of the lattice energy absorbing structure and the mixing tube after compression alone with the mixing tube after filling. Figure 6 From the results shown, it can be found that the quasi-static test results of the 100mmHQLS lattice energy absorption structure are not much different from the simulation results. Figure 5 As shown in the figure, it can be found that during the compression process, the deformation of the lattice energy absorption structure starts from both ends and gradually concentrates to the middle, and the upper lattice energy absorption structure is compacted first. During the compression process, the HQLS lattice energy absorption structure showed obvious convexity, but no cracking occurred. The errors between the various mechanical parameters of the quasi-static compression test and finite element simulation of the 100mm high HQLS lattice energy absorption structure are shown in Table 3, with a maximum of 3.9%, proving that the finite element model of the lattice structure has a high accuracy.
[0027] Table 3 Comparison of the accuracy of the test and finite element model of the HQLS lattice energy absorption structure at a height of 100 mm
[0028] Therefore, the above-mentioned six-deformation-quadrilateral lattice energy absorption structure is adopted, based on the secondary design of the flat-top pyramid, the bottom shape of the cell unit is adjusted and the connection between the cell units is optimized, which improves the energy absorption capacity of the lattice energy absorption structure and ensures the energy absorption performance of the lattice energy absorption structure. It is particularly suitable for application scenarios that require high specific energy absorption and good stability.
[0029] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A six-deformation quadrilateral lattice energy absorption structure, based on a flat-top pyramid structure for secondary design, It is characterized in that The lattice energy absorption structure is formed by a plurality of interconnected cell units distributed in an array along the z-axis, each of the cell units has a hexagonal bottom surface and a quadrilateral top surface, and the structural shape of the entire cell unit is a prism.
2. A six-deformation-quadrangular lattice energy absorption structure according to claim 1, It is characterized in that The length, width and height of each cell unit are limited to 10×10×10mm. 3 The structure is in a cube, and the thickness of each cell unit is 1 mm.
3. A six-deformation-quadrangular lattice energy absorption structure according to claim 2, It is characterized in that The tops of the cell units are inscribed in 5×5mm 2 The cell units are arranged in a square, and each of the cell units has a height of 10 mm and a total height of 40 mm.
4. The six-deformation-quadrangular lattice energy absorption structure according to claim 1, It is characterized in that The hexagonal bottom surface is circumscribed to a square, the shape of the quadrilateral top surface is a square, and the side length of the quadrilateral top surface is smaller than the side length of the circumscribed square of the hexagonal bottom surface.
5. A six-deformation-quadrangular lattice energy absorption structure according to claim 4, It is characterized in that The side length of the hexagonal bottom surface and the side length of the quadrilateral top surface of the cell unit are both 5 mm.
6. The six-deformation-quadrangular lattice energy absorption structure according to claim 1, It is characterized in that The edges of each cell unit are closely connected to the edges of adjacent cell units to form a close-fitting arrangement structure, so as to improve the energy absorption capacity of the structure by increasing plastic hinges.
Citation Information
Patent Citations
Honeycomb-like sandwich structure
CN103559343A
Irregular cellular-oriented sandwich type composite structure design method
CN107301273A
Recoverable deformation automobile energy absorption box based on additive manufacturing
CN112428949A
Energy absorption element and dot matrix energy absorption structure thereof
CN113392551A
Buffer material, buffer structure, sole, and shoe
CN114746668A
